Bifidobacterium infantis Metabolizes 2′Fucosyllactose-Derived and Free Fucose Through a Common Catabolic Pathway Resulting in 1,2-Propanediol Secretion - Dedon, Liv R.; Özcan, Ezgi; Rani, Asha; Sela, David A. (Frontiers in Nutrition, 2020)
Human milk oligosaccharides (HMOs) enrich beneficial bifidobacteria in the infant gut microbiome which produce molecules that impact development and physiology. 2´fucosyllactose (2´FL) is a highly abundant fucosylated HMO which is utilized by Bifidobacterium longum subsp. infantis, despite limited scientific understanding of the underlying mechanism. Moreover, there is not a current consensus on whether free fucose could be metabolized when not incorporated in a larger oligosaccharide structure. Based on metabolic and genomic analyses, we hypothesize that B. infantis catabolizes both free fucose and fucosyl oligosaccharide residues to produce 1,2-propanediol (1,2-PD). Accordingly, systems-level approaches including transcriptomics and proteomics support this metabolic path. Co-fermentation of fucose and limiting lactose or glucose was found to promote significantly higher biomass and 1,2-PD concentrations than individual substrates, suggesting a synergistic effect. In addition, and during growth on 2´FL, B. infantis achieves significantly higher biomass corresponding to increased 1,2-PD. These findings support a singular fucose catabolic pathway in B. infantis that is active on both free and HMO-derived fucose and intimately linked with central metabolism. The impact of fucose and 2´FL metabolism on B. infantis physiology provides insight into the role of fucosylated HMOs in influencing host- and microbe-microbe interactions within the infant gut microbiome.